AEG -1 Overexpression: A Novel Indicator for Peritoneal Dissemination and Lymph Node Metastasis in Epithelial Ovarian Cancers. Issue 4 (1st April 2011) - Li, Cong; Liu, Junjun; Lu, Renbo; Yu, Ge; Wang, Xiaochuan; Zhao, Yulan; Song, Hongtao; Lin, Ping; Sun, Xicai; Yu, Xiaoguang; Zhang, Yuan; Ning, Xiaoming; et al.
Abstract : Objective: Despite advances in chemotherapy and cytoreductive surgery, ovarian cancer remains the most lethal gynecological malignancy with a 5-year survival rate of 25% to 30% in advanced stage disease. Our purpose is to evaluate whether astrocyte elevated gene-1 (AEG-1) is a novel predictor of peritoneal dissemination and lymph node metastasis in epithelial ovarian cancer (EOC), which was not previously studied by others. Materials and Methods: Through immunohistochemical and Western blot analysis, AEG-1 expression was evaluated in 25 normal ovarian and 157 EOC specimens. The relationship between AEG-1 expression and EOC metastasis was determined by univariate and multivariate analyses. Results: Western blotting analysis revealed that AEG-1 was overexpressed in metastatic tissues from patients with ovarian cancers. Immunohistochemistry results showed that 83 (95.4%) presented peritoneal dissemination; 41 (47.1%) had lymph node metastasis among 87 patients with AEG-1 overexpression. Univariate and multivariate logistic regression analyses demonstrated that AEG-1 overexpression correlated with peritoneal dissemination and lymph node metastasis in EOC. We further found that the positive and specificity predictive value of AEG-1 staining were better for peritoneal metastasis, whereas the negative and sensitivity predictive value of AEG-1 staining were better for lymph node metastasis. The odds ratio of high-to-low expression for peritoneal dissemination was 8.541 (95% confidence interval, 2.561-37.461), and that for lymph node metastasis was 9.581 (95% confidence interval, 2.613-23.214). Conclusions: The present findings indicate that AEG-1 is overexpressed in a great portion of EOC patients with peritoneal dissemination and/or lymph node metastasis and may be clinically useful for predicting metastasis in EOC. Our findings might provide some benefits for metastatic EOC patients in the clinic.